Determination of the Optimum Values of the Natural Frequency of the Nanocomposite Multilayer Organic Solar Cell by using Basic Differential Evolution Optimization Algorithms - Minh Anh, Vu (VNU Journal of Science: Mathematics - Physics; Vol 39 No 1DO - 10.25073/2588-1124/vnumap.4773, 2023)
By the analytical approach, the equation of natural frequency of nanocomposite multilayer organic solar cell (NMOSC) is analyzed in this work. The NMOSC is composed of 6 layers: Al, LiF, P3HT: PCBM, PEDOT: PSS, ITO and Glass. By using the classical plate theory, the Hooke’s Law, the geometrical compatibility equation and the nonlinear equilibrium equations are proposed. These equations combined with the Galerkin method in order to investigate the effect of elastic foundations, geometrical parameters and initial imperfection on the natural frequency. Besides, in order to determine the maximum natural frequency of NMOSC, basic differential evolution optimization algorithm (DE) was used with five variables: elastic foundations include Winkeler foudation and Pasternak foudation, temperature, width and length. In the numerical results, the influence of length to width ratio, imperfection, elastic foundations and temperature increment were evaluated in detail. The optimal results from DE algorithm are shown and compared.